Генетичний аналіз поліморфізму Val89Leu гена SRD5α2 та гена SRY у пацієнтів з порушенням диференціації статі - Тиркус, М.Я.; Макух, Г.В.; Тенета, М.М.; Шуварська, В.І.; Заставна, Д.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. 5α-reductase is an enzyme that converts testosterone to 5α-dihydrotestosterone (DHT) in peripheral tissues. Deficiency of the enzyme 5α-reductase causes a disturbance of the formation of the external genitalia before birth. The polymorphism Val89Leu of SRD5α2 gene is associated with decreased activity of the enzyme 5-alpha-reductase-2. Methods. DNA from probands blood samples was isolated using a modified salting out method. Microdeletions of Y‑chromosome AZF regionand SRY gene were analyzed using two multiplex PCR. The PCR products were digested with the restriction enzyme Rsa I and analyzed by electrophoresis in a 2% agarose gel. Results. In 20 newborn children with violation of sex differentiation was set male and found no genetic disorders in region of AZF Y-chromosome. Among men in the our study group homozygous genotype LeuLeu (CC) polymorphic loci Val89Leu of SRD5α2 gene was found in 45%, which is associated with a deficiency of 5-alpha-reductase. Conclusions. The results of the study polymorphic loci Val89Leu of 5-alpha-reductase-2 gene in patients with violation of sex differentiation showed that homozygous genotype LeuLeu (CC) polymorphic loci Val89Leu be a probable genetic differentiation factors violation sex. Keywords: Y-chromosome, polymorphism, sex determination, SRD5α2 gene.